Alteration of Membrane Fluidity or Phospholipid Composition Perturbs Rotation of MreB Complexes in Escherichia coli - Kurita, Keisuke; Kato, Fumiya; Shiomi, Daisuke (Frontiers in Molecular Biosciences, 2020)
Gram-negative bacteria such as Escherichia coli are surrounded by inner and outer membranes and peptidoglycan in between, protecting the cells from turgor pressure and maintaining cell shape. The Rod complex, which synthesizes peptidoglycan, is composed of various proteins such as a cytoplasmic protein MreB, a transmembrane protein RodZ, and a transpeptidase PBP2. The Rod complex is a highly motile complex that rotates around the long axis of a cell. Previously, we had reported that anionic phospholipids (aPLs; phosphatidylglycerol and cardiolipin) play a role in the localization of MreB. In this study, we identified that cells lacking aPLs slow down Rod complex movement. We also found that at higher temperatures, the speed of movement increased in cells lacking aPLs, suggesting that membrane fluidity is important for movement. Consistent with this idea, Rod complex motion was reduced, and complex formation was disturbed in the cells depleted of FabA or FabB, which are essential for unsaturated fatty acid synthesis. These cells also showed abnormal morphology. Therefore, membrane fluidity is important for maintaining cell shape through the regulation of Rod complex formation and motility.